2022
DOI: 10.3390/ijerph19137982
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Adverse Drug Reactions (CADRs)—Statistical Analysis of the Causal Relationship between the Drug, Comorbidities, Cofactors, and the Cutaneous Reaction—A Single-Centered Study

Abstract: Cutaneous adverse drug reactions (CADRs) are among the most common types of drug hypersensitivity reactions. The purpose of this study was to evaluate the clinical spectrum of CADRs and to determine the causal relationship between drugs, comorbidities, cofactors or concomitant symptoms, and cutaneous reactions. A retrospective hospital-based study was carried out over a period of 10 years at the Department of Dermatology, Sexually Transmitted Diseases and Clinical Immunology at the University of Warmia and Maz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…In almost all the papers, ABs were one of the major causes of cADRs or ScADRs. The lowest frequency was found to be between 5% -10% [15,26,42] and highest being 81.13% [70] followed by 73.8% [71]. Several other studies also found a very high frequency of AB-associated cADRs like- Wong et al, (2019) [72] 66.1%, Dimri, Raina, Thapliyal, & Thawani, (2016) >69% [11], and Verma et al, 56% [73] (Table 2).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In almost all the papers, ABs were one of the major causes of cADRs or ScADRs. The lowest frequency was found to be between 5% -10% [15,26,42] and highest being 81.13% [70] followed by 73.8% [71]. Several other studies also found a very high frequency of AB-associated cADRs like- Wong et al, (2019) [72] 66.1%, Dimri, Raina, Thapliyal, & Thawani, (2016) >69% [11], and Verma et al, 56% [73] (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…It is a delayed hypersensitivity reaction. There are pruritic, erythematous skin eruptions, especially on the flexural intertriginous areas [42] like inguinal and/or gluteal regions. Well-demarcated lesions with eczema, scaling or desquamation of affected skin are common features.…”
Section: Symmetric Drug-related Intertriginous and Flexural Erythema/...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the prevalence of immunosuppression, malignancy, and autoimmune disease in our patient population was quite high (47%, 47%, and 18%, respectively). While our case population was drawn exclusively from a single academic tertiary‐care facility, and thus likely overrepresents more complex and hospitalized patients, these numbers are still notably high, even compared to other studies of CADRs 28–30 . The immune dysregulation seen in these conditions is believed to be a major contributor to CADR development 15 .…”
Section: Discussionmentioning
confidence: 98%
“…While our case population was drawn exclusively from a single academic tertiary‐care facility, and thus likely overrepresents more complex and hospitalized patients, these numbers are still notably high, even compared to other studies of CADRs. 28 , 29 , 30 The immune dysregulation seen in these conditions is believed to be a major contributor to CADR development. 15 Determining specific diagnostic criteria for drug eruption is especially important for these patients, as CADR may present similarly to other serious conditions requiring specific management, including paraneoplastic syndromes, autoimmune diseases, GvHD, and infections.…”
Section: Discussionmentioning
confidence: 99%